E-COMMERCE UTILIZATION EFFORTS ENTREPRENEURS IN INDONESIA - Meilisa, Meilisa; Bachtiar, Nasri; Taifur, Werry Danar; Ridwan, Endrizal (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
To increase competitive advantage and expand markets, digitalization brings new trends with technological innovation in the form of e-commerce. Using Sakernas data for 2021, the research intends to analyze the impact of using e-commerce on business actors between two groups, namely business actors using e-commerce and those without using e-commerce for their business. The selected sample in the research was business actors who did not yet have permits for their business activities, namely 36,703. The e-commerce category is: product promotion with internet coverage, and sales carried out through marketplaces (Tokopedia, Bukalapak, Olx, etc). The results show that business actors who utilize e-commerce have higher income than business actors without using e-commerce in their business, which is influenced by human capital (education), digital skills (use of computers and smartphones), socio-demographics (age, gender), with the Propensity Score Matching (PSM) method.